Aqueous passivation of multi-principal element alloy Ni38Fe20Cr22Mn10Co10: Unexpected high Cr enrichment within the passive film. (1st October 2020) - Gerard, Angela Y.; Han, Junsoo; McDonnell, Stephen J.; Ogle, Kevin; Kautz, Elizabeth J.; Schreiber, Daniel K.; Lu, Pin; Saal, James E.; Frankel, Gerald S.; Scully, John R.
Abstract: The aqueous passivation of a non-equiatomic Ni38 Fe20 Cr22 Mn10 Co10 - at.% (Ni40 Fe20 Cr20 Mn10 Co10 - wt.%) multi-principal element alloy (MPEA) was investigated in 0.1 M NaCl at pH 4 and compared to a conventional binary Ni76 Cr24 – at.% (Ni78 Cr22 – wt.%) alloy. The electrochemical behavior and oxide film characteristics were explored utilizing in-situ electrochemical and ex-situ surface-sensitive techniques. The passive film composition, thickness, and elemental valence states, as well as, the fate of each element were studied by in-situ atomic emission spectro-electrochemistry, ex-situ X-ray photoelectron spectroscopy, and atom probe tomography. The Ni38 Fe20 Cr22 Mn10 Co10 MPEA demonstrated slightly better corrosion resistance compared to the binary Ni76 Cr24, alloy. Passive films on the MPEA contained primarily Cr, and small amounts of Ni, Fe, Co and Mn, while dissolution of Ni, Fe, Co was observed. Ni 0 was enriched at the oxide/metal interface while Cr was depleted. Enrichment of Cr in the passive film occurred to a greater extent in the MPEA than for the Ni-Cr binary alloy. Enrichment factors were determined and the origins of enrichment are discussed. Graphical abstract: Image, graphical abstract